Electronic devices and circuits - Parasuram, M. (Engineering series, 2012)
Electronic Devices & Circuits is part of the Engineering Series published specifically for Technical and Engineering students and those with interest in this subject. The main objective of this book is to provide a basic knowledge in electronic devices and circuits, in a very simple, lucid and understandable language. This book offers an excellent coverage of all essential topics and provides a solid foundation for analyzing electronic circuits. Each chapter is well planned and the lucid style of narration will make the students grasp the idea easily. Numerous tables, diagrams and illustrations are used to further explain the subject for easy comprehension of the reader.